Financial Deepening, Terms of Trade Shocks, and Growth Volatility in Low-Income Countries - Roland Kangni Kpodar; Maëlan Le Goff; Raju Jan Singh (Fondation pour les études et recherches sur le développement international (FERDI), 2018)
This paper contributes to the literature by looking at the possible importance of the structure of the financial system—whether financial intermediation is performed through banks or markets—for macroeconomic volatility, against the backdrop of increased policy attention on strengthening growth resilience. With low income countries (LICs) being the most vulnerable to large and frequent terms of trade shocks, the paper focuses on a sample of 38 LICs over the period 1978-2012 and finds that banking sector development acts as a shock absorber, dampening the transmission of terms of trade shocks to growth volatility. Expanding the sample to 121 developing countries confirms this result, although this role of shock-absorber fades away as economies grow richer. Stock market development, by contrast, appears neither to be a shock absorber nor a shock amplifier for most economies. These findings are robust across fixed effect, System GMM and local projection estimates.
Keywords: F40; G20; O10; 330; Banks; stock markets; terms of trade; growth volatility